A transgenerational role of the germline nuclear RNAi pathway in repressing heat stress-induced transcriptional activation in C. elegans. Issue 1 (December 2016) - Ni, Julie; Kalinava, Natallia; Chen, Esteban; Huang, Alex; Trinh, Thi; Gu, Sam
Abstract Background Environmental stress-induced transgenerational epigenetic effects have been observed in various model organisms and human. The capacity and mechanism of such phenomena are poorly understood. InC. elegans, siRNA mediates transgenerational gene silencing through the germline nuclear RNAi pathway. This pathway is also required to maintain the germline immortality whenC. elegans is under heat stress. However, the underlying molecular mechanism is unknown. In this study, we investigated the impact of heat stress on chromatin, transcription, and siRNAs at the whole-genome level, and whether any of the heat-induced effects is transgenerationally heritable in either the wild-type or the germline nuclear RNAi mutant animals. Results We performed 12-generation temperature-shift experiments using the wild-typeC. elegans and a mutant strain that lacks the germline-specific nuclear Argonaute protein HRDE-1/WAGO-9. By examining the mRNA, small RNA, RNA polymerase II, and H3K9 trimethylation profiles at the whole-genome level, we revealed an epigenetic role of HRDE-1 in repressing heat stress-induced transcriptional activation of over 280 genes. Many of these genes are in or near LTR (long-terminal repeat) retrotransposons. Strikingly, for some of these genes, the heat stress-induced transcriptional activation in thehrde -1 mutant intensifies in the late generations under the heat stress and is heritable for at least two generations after the mutant animals are shifted back to lower temperature.hrde -1 mutation also leads to siRNA expression changes of many genes. This effect on siRNA is dependent on both the temperature and generation. Conclusions Our study demonstrated that a large number of the endogenous targets of the germline nuclear RNAi pathway inC. elegans are sensitive to heat-induced transcriptional activation. This effect at certain genomic loci including LTR retrotransposons is transgenerational. Germline nuclear RNAi antagonizes this temperature effect at the transcriptional level and therefore may play a key role in heat stress response inC. elegans .